2017
DOI: 10.3892/or.2017.5979
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-1297 inhibits metastasis and epithelial-mesenchymal transition by targeting AEG-1 in cervical cancer

Abstract: Abstract. Accumulating evidence has demonstrated that aberrant miRNAs contribute to cervical cancer (CC) development and progression. However, the roles of various miRNAs in CC remain to be determined. In the present study, we confirmed that a decreased miR-1297 expression was present in CC tissues and cell lines. Our clinical analysis revealed that the downregulated miR-1297 expression was significantly correlated with poor prognostic features including lymph node metastasis and lymphovascular space invasion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…AEG-1, also known as metadherin (MTDH), and lysine-rich CEACAM1 co-isolate protein (LYRIC) greatly participate in carcinogenesis and tumor progression in several malignancies. Fortunately, it was also discovered by Wang et al [129] that alteration of AEG-1 eliminates the suppressive effects of miR-1297 on the metastasis of CC and EMT. The down-regulation of miR-145 might generate EMT and the metastasis of CC in conjunction with up-regulated expression of SMAD-interacting protein 1 (SIP1, also known as ZEB2) [130].…”
Section: The Role Of Emt-related Mirnas In the Metastasis Of CCmentioning
confidence: 99%
See 1 more Smart Citation
“…AEG-1, also known as metadherin (MTDH), and lysine-rich CEACAM1 co-isolate protein (LYRIC) greatly participate in carcinogenesis and tumor progression in several malignancies. Fortunately, it was also discovered by Wang et al [129] that alteration of AEG-1 eliminates the suppressive effects of miR-1297 on the metastasis of CC and EMT. The down-regulation of miR-145 might generate EMT and the metastasis of CC in conjunction with up-regulated expression of SMAD-interacting protein 1 (SIP1, also known as ZEB2) [130].…”
Section: The Role Of Emt-related Mirnas In the Metastasis Of CCmentioning
confidence: 99%
“…With regard to the diagnosis and treatment of metastatic CC, researchers have studied cervical tissues and found a relationship between miRNAs and the diagnosis and treatment of metastatic CC. It was of interest to find that decreased miR-99a/b [90], miR-125a [139], miR-138 [75], miR-140-5p [85], miR-144 [66], miR-195 [127], miR-205 [88], miR-214 [91], miR-218 [96,133,148,167], miR-329-3p [57], miR-337 [68], miR-362 [94], miR-374c-5p [143], miR-375 [67], miR-377 [126], miR-379 [104], miR-485 [105], miR-486-3p [62], miR-638 [123], and miR-1297 [129] expression strongly correlate with tumor size, TNM stage, tissue pathology grade, International Federation of Gynecology and Obstetrics (FIGO) stage, lymph node metastasis, or distant metastasis in patients with CC. In addition, overexpressed miR-20a [31], miR-21 [168], miR-92a [118], miR-145 [79], miR-195 [166], miR-199b-5p [169], and miR-501 [51] closely correlate with histological grade, tumor diameter, overall survival (OS), progression-free survival (PFS), late FIGO stages, lymph node metastasis, or preoperative metastasis.…”
Section: The Role Of Hpv-related Mirnas In the Metastasis Of CCmentioning
confidence: 99%
“…The metastasis of cervical cancer is a process concerning multi-factor, multi-step, and continuous cascade reactions [4]. In the study of cervical cancer metastasis, epithelial-mesenchymal transition (EMT), as the key link in the metastatic cascade, has attracted more and more attention from scholars at home and abroad [5,6].…”
Section: Introductionmentioning
confidence: 99%
“… 17 Wang et al found that miR-1297 inhibited metastasis by targeting AEG-1 in cervical cancer. 18 Wang et al reported that serum miR-1297 is a promising diagnostic biomarker in esophageal squamous cell carcinoma. 19 Therefore, miR-1297 is an effective target for the treatment of tumors.…”
Section: Discussionmentioning
confidence: 99%